1996
DOI: 10.1063/1.117607
|View full text |Cite
|
Sign up to set email alerts
|

Very high breakdown voltage and large transconductance realized on GaN heterojunction field effect transistors

Abstract: We report record high breakdown voltages up to 340 and 230 V realized on unintentionally doped (1.5 μm gate length) and Si doped (1 μm gate length) AlGaN/GaN modulation doped field effect transistors (MODFETs), respectively. The devices also have large transconductances up to 140 mS/mm and a full channel current of 150–400 mA/mm. The Si doped MODFET sample demonstrated a very high room temperature mobility of 1500 cm2/Vs. With these specifications, GaN field effect transistors as microwave power devices are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
127
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 346 publications
(134 citation statements)
references
References 0 publications
5
127
1
1
Order By: Relevance
“…This is an order of magnitude faster than for other semiconductors. Diodes that emit blue light [1], multi quantum well laser diodes [2], and high speed field effect transistors [3] have already been fabricated on the basis of these structures. These are promising for the development of highly sensitive sensors [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is an order of magnitude faster than for other semiconductors. Diodes that emit blue light [1], multi quantum well laser diodes [2], and high speed field effect transistors [3] have already been fabricated on the basis of these structures. These are promising for the development of highly sensitive sensors [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Promising applications of the high possibilities for high-power and high-speed operations require important information of the electronic parameters affecting the carrier density and the mobility of the two-dimensional electron gas (2DEG) occupying the Al x Ga 1−x N/GaN heterostructure because a large carrier density and high mobility of the 2DEG are necessary for achieving high efficiency devices. 6 Recently, it is found that the carrier density and mobility of the 2DEG occupying the Al x Ga 1−x N/GaN heterostructures could be significantly improved by inserting an AlN interlayer.…”
Section: Introductionmentioning
confidence: 99%
“…Group III nitride semiconductors and their heterostructures have recently attracted much attention for their versatile applications as light emitting devices, solar-blind ultraviolet detectors, and high power/high temperature/high frequency devices [1][2][3][4][5][6]. Much interest has been focused on InGaN/GaN quantum wells (QWs) because of their applications as high brightness light emitting diodes and cw blue laser diodes [1,2].…”
Section: Introductionmentioning
confidence: 99%